A retrospective comparative study of microwave ablation and sublobectomy in the treatment of early subpleural nonsmall cell lung cancer - Jianwei Liu; Caixia Wang; Weiwei Yi; Hang Zheng; Aimin Zheng (International Journal of Hyperthermia)
Objective Microwave ablation (MWA) is a safe and effective local therapy, however, its efficacy in stage I subpleural nonsmall cell lung cancer (NSCLC) compared to that of sublobar resection (SLR) is unclear. This study aimed to compare the efficacy of the two treatments for stage I NSCLC ≤1 cm from the pleura.Methods After propensity score matching (PSM), 70 patients with stage I subpleural NSCLC who underwent either SLR or MWA (35 patients each) from 2014 to 2018 were included. The margin pathology of SLR was negative. MWA reached a sufficient ablative margin. MWA group were stratified according to the minimal ablative margin, with 10 patients each in the 5–10 mm group and the >10 mm group after PSM. The local recurrence-free survival (LRFS), relapse-free survival (RFS), overall survival (OS), and treatment-related complications were compared.Results For patients with stage I subpleural NSCLC, the LRFS of patients in the SLR group (35.657 ± 0.338 months, 95% CI: 34.995–36.319) was significantly better than that in the MWA group (31.633 ± 1.574 months, 95% CI: 28.548–34.719, p = 0.021). The RFS was also significantly better in the SLR group (35.629 ± 0.338 months, 95% CI: 34.966–36.292) than in the MWA group (29.387 ± 1.866 months, 95% CI: 25.730–33.044, p = 0.007), but there were no significant differences in terms of the 3-year OS (p = 0.079) and incidence of complications (14.3% vs. 11.4%, p = 0.653). The minimal ablative margin of >10 mm was not significantly associated with the LRFS (p = 0.929).Conclusion MWA for stage I subpleural NSCLC showed similar survival outcomes and complication rates to SLR, but poorer local tumor control.